Синтез та антимікробна активність похідних етил 5-метил-2-(алкілтіо)-4-оксо-3,4-ди-гідротієно[2,3-d]піримідин-6-карбоксилатів - Tkachenko, O. V.; Vlasov, S. V.; Kovalenko, S. M.; Zhuravel’, I. O.; Chernykh, V. P. (National University of Pharmacy, 2013)
By alkylation of the products of diethyl 3-methyl-5 {[(methylthio)carbonothioyl]amino}-2,4-thiophenedicarboxylate interactionwith benzylamines the novel derivatives of ethyl 5-methyl-2-(alkylthio)-4-oxo-3,4-dihydrothieno[2,3-d]pyrimidine-6-carboxylates have been obtained. It has been found that the signal of the CH2-group adjacent to the nitrogen atom in position 3 of thieno[2,3-d]pyrimidine system is always observed in the range of 5.35-5.40 ppm, while the position of the signal of methythylene-group connected with the sulfur atom much depends upon the structure of the radical attached to this group. IR-spectra of all the compounds contain the intensive С=О stretching band at 1721-1678 cm-1; the spectra of the compounds with amide function contain bands of stretching N–H of 3280-3263 cm-1, while nitriles have the band of stretching C≡N vibrations near 2250 сm-1. It has been determined that all of the compounds are mostly active against the strain of Candida aibicans fungi. The most resistant microorganism was found to be the strains of Staphylococcus aureus. The only exception is the derivative modified with the thioacetic acid residue in position 2 and unsubstituted benzyl in position 3, which appeared to be highly active against Staphylococcus aureus strain. Amides of thioactetic acid modified in position 3 with 3,4-dichlorobenzyl substituent and thioacetamide substituents in position 2 are active against Pseudomonas aeruginosa, as well as the compound, which contains 3-chlorobenzyl substituent in position 3 and p-chlorobenzotiol substituents in position 2 of thieno[2,3-d]pyrimidine.